Current Legal Issues Affecting Central Banks, Volume IV. : Volume IV. - Effros, Robert (International Monetary Fund, 1997)
This volume, edited by Robert C. Effros, surveys developments at international financial institutions, regional developments affecting central banks, the progress of the European Union countries toward monetary union and a unified banking market, the effect of the General Agreement on Tariffs and Trade and the World Trade Organization on banking services, and the implications of the North American Free Trade Agreement for central banks. Other topics discussed include banking regulation and reform in the United States, the United Kingdom, Canada, countries of the former Soviet Union, and China; banking supervision; the role of deposit insurance; bankruptcy policy; derivatives; securitization; payments systems; securities transfers; and capital standards for market risk. Appendices reproduce relevant legal documentation.